2008
DOI: 10.1074/mcp.m700314-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Approach to Identify Dehydration Responsive Nuclear Proteins from Chickpea (Cicer arietinum L.)

Abstract: Dehydration or water-deficit is one of the most important environmental stress factors that greatly influences plant growth and development and limits crop productivity. Plants respond and adapt to such stress by altering their cellular metabolism and activating various defense machineries. Mechanisms that operate signal perception, transduction, and downstream regulatory events provide valuable information about the underlying pathways involved in environmental stress responses. The nuclear proteins constitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
151
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(158 citation statements)
references
References 91 publications
4
151
0
3
Order By: Relevance
“…This is a clear indication of the dehydration-induced increase in concentration of a wRKY TF in the nucleus and suggests that this wRKY is regulated by water stress (Choudhary et al 2009). excitingly, a similar study of the dehydration-responsive nuclear proteome of chickpea (Pandey et al 2008) from the same group also identified a similar wRKY protein that is upregulated by dehydration in chickpea. The chickpea wRKY protein appears to be an ortholog of the Arabidopsis group I protein, AtwRKY4.…”
Section: Proteomicsmentioning
confidence: 81%
“…This is a clear indication of the dehydration-induced increase in concentration of a wRKY TF in the nucleus and suggests that this wRKY is regulated by water stress (Choudhary et al 2009). excitingly, a similar study of the dehydration-responsive nuclear proteome of chickpea (Pandey et al 2008) from the same group also identified a similar wRKY protein that is upregulated by dehydration in chickpea. The chickpea wRKY protein appears to be an ortholog of the Arabidopsis group I protein, AtwRKY4.…”
Section: Proteomicsmentioning
confidence: 81%
“…We also identified a transcription factor homologous to Arabidopsis MYB24, which plays a role in anther development (Matus et al, 2008). Topic 2 (leaves undergoing senescence) was characterized by the strong expression of stress response genes, including those encoding several ribosomal proteins and histones that may control stress-induced gene expression and protein synthesis (Pandey et al, 2008;Falcone Ferreyra et al, 2010), abiotic stress response enzymes, such as stilbene synthase, glutathione S-transferase (oxidative stress), and EARLY LIGHT-INDUCED PROTEIN1 (illumination stress), and pathogen response factors, including metallothionein (Breeze et al, 2011), PATHOGENESIS-RELATED10-like proteins, and two ADP-ribosylation factors (Nomura et al, 2011). Samples from mature/woody samples were distributed over three topics: ripening berries (topic 3), withering berries (topic 5), and veraison and mid-ripening seeds, winter buds, and woody stems (organs related to woody structures or to the dormant state; topic 4).…”
Section: Division Of Samples Into Topics Defined By High-level Gene Ementioning
confidence: 99%
“…In addition, a few EST projects have provided a few thousand singlepass sequences (Buhariwalla et al, 2005;Gao et al, 2008;Ashraf et al, 2009;Varshney et al, 2009;Jain and Chattopadhyay, 2010). Although several genes/ESTs involved in various stress responses have been identified based on transcriptomic and proteomic studies (Pandey et al, 2006(Pandey et al, , 2008Mantri et al, 2007;Molina et al, 2008Molina et al, , 2011Varshney et al, 2009), the gene discovery has been very limited in chickpea. So far, only a few candidate genes have been cloned and functionally validated (Kaur et al, 2008;Shukla et al, 2009;Tripathi et al, 2009;Peng et al, 2010).…”
mentioning
confidence: 99%